THE NECESSITY OF FORMING AN INFORMATION CULTURE IN PRIMARY SCHOOL STUDENTS IN A DIGITAL SOCIETY - Ubaydullaeva Sharofat (Uzbekistan Open Conference, 2025)
This article analyzes the role of information culture in society and the education system in the era of globalization and digital transformation from a scientific and theoretical point of view. Information culture is defined as a person's ability to search for, analyze, critically evaluate, process, and disseminate information in accordance with ethical norms. The study compares the scientific approaches of Western, Russian, and Uzbek scholars to information culture and substantiates the multifaceted nature of this concept - information literacy, technological competence, information ethics, and elements of critical thinking.
Keywords: information culture; digital literacy; media literacy; information security; primary education; digital transformation; critical thinking; information ethics; ICT; teacher competence; digital culture; information space; pedagogical process; digital competence; interactive learning